2011
DOI: 10.1007/s12253-011-9364-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunoexpression of SALL4 in Wilms Tumors and Developing Kidney

Abstract: SALL4 is a zinc finger transcription factor that plays a role in the maintainance and pluripotency of embryonic stem cell and is important in renal development where SALL4 mutations give rise to renal malformations. Because Wilms tumor recapitulates renal embryogenesis, we hypothesized that Wilms tumor cells may also express SALL4. We performed immunohistochemistry for SALL4 on tissue microarray sections of Wilms tumors, nephrogenic rests, and fetal renal cortices. Half (26 out of 52) of the Wilms tumors showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…SALL4 is a recently described marker for the epithelial component of human WTs, and these tumors stained weakly positive for this by IHC staining ( Figure 3G). 53 Taken together, the expression pattern of these tumors reflects their epithelial dominance and suggests features that have been identified in some human WTs. Figure 4A).…”
Section: ␤-Catenin and K-ras In Wilms' Tumors 3049mentioning
confidence: 59%
“…SALL4 is a recently described marker for the epithelial component of human WTs, and these tumors stained weakly positive for this by IHC staining ( Figure 3G). 53 Taken together, the expression pattern of these tumors reflects their epithelial dominance and suggests features that have been identified in some human WTs. Figure 4A).…”
Section: ␤-Catenin and K-ras In Wilms' Tumors 3049mentioning
confidence: 59%
“…In primary acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS), the expression of SALL4 is higher than health control. At the meaning time, some other kinds of tumor such as colorectal cancer, breast cancer, and Wilms tumors also express SALL4 [4, 7, 8]. More recently, SALL4 has been suggested as a marker of germ cell tumor, including primary and metastatic of yolk sac tumor [913].…”
Section: Introductionmentioning
confidence: 99%
“…11,12 After birth, SALL4 expression is down-regulated and absent in most adult tissues. However, SALL4 is expressed in various cancers, including a subset (30%) of solid tumors such as breast cancer, 13 ovarian cancer, 14 gastric cancer, 15 Wilms tumor, 16 and germ cell tumors, 14,[17][18][19][20][21] as well as in leukemias-most notably, almost all cases of human acute myeloid leukemia (AML) 22 and approximately 75% of B-cell acute lymphoblastic lymphoma/ leukemia. 23 We have also reported that SALL4 is enriched in the "side-population" of the leukemia and solid tumor cells.…”
Section: Introductionmentioning
confidence: 99%